Optimization of parameters of multilayer diffraction gratings using needle variations - V.Yu. Martynova; Yu.G. Smirnov; A.V. Tikhonravov (Известия высших учебных заведений. Поволжский регион: Физико-математические науки, 2022)
Background. The purpose of the work is to optimize the diffraction efficiency in the first diffraction order of a multilayer diffraction grating. Material and methods. Needle variations are used to optimize diffraction efficiency. Results. Computational experiments were performed, which showed that the addition of a second line in the grating period significantly increased the diffraction efficiency in the first diffraction order. Conclusions. The use of needle variations is applicable in the design of multilayer diffraction gratings.